Head Enlargement in Infants Requiring Neurosurgical Care - Sangh Mittra; Rajnish Arora; Intezar Ahmed; Raj Kumar (Indian Journal of Neurosurgery)
Abstract Head enlargement (macrocephaly) is not an uncommon neurosurgical condition in infants presenting to outpatient department and emergency departments of neurosurgery/gynecology/pediatrics. We conducted a prospective and retrospective study of head enlargement in infants requiring neurosurgical care, to establish etiology, imaging findings, clinical profile, and outcome, with emphasis on management. Over a period of 24 months, 65 cases presented with head enlargement. All had a history of cranial expansion from neonatal period. Of 65 patients, 30 could match the inclusion criteria and were selected for this study. Age group ranged from 151 to 180 days, consisted maximum numbers (n = 10; 33.3%) of cases; of 30 23 (76.7%) patients were males. Of 30, 21 (70%) patients were diagnosed to have hydrocephalus, 4 (13.3%) had Dandy–Walker malformation, 2 (6.7%) had subdural effusion, and 3 cases (10%) had other causes as primary diagnoses. All were offered standard treatment as described in literature according to their clinical conditions and stage of diseases which included shunts (ventriculoperitoneal—unilateral, biventricular, and cystoventriculoperitonal), Ommaya placement, craniotomy, burr holes, and conservative. Four shunts required revision during follow-up period. The postoperative follow-up period ranged from 1 to 24 months. One child with the diagnosis of intracranial tumor died in postoperative period that is 1 month after the surgery due to disease-related morbidities. Thus, there are various causes of head enlargement in neonates where neurosurgical intervention may be required, the most common being the hydrocephalus, Dandy–Walker malformation followed by subdural effusion. The treatment depends on the diagnosis. Benign conditions such as subdural effusion do not require surgical intervention usually.